Daily tracker of global economic activity: A close-up of the COVID-19 pandemic - Elena Diaz; Gabriel Pérez-Quirós (European Central Bank (ECB), 2020)
This paper develops a novel indicator of global economic activity, the GEA Tracker, which is based on commodity prices selected recursively through a genetic algorithm. The GEA Tracker allows for daily real-time knowledge of international business conditions using a minimum amount of information. We find that the GEA Tracker outperforms its competitors in forecasting stock returns, especially in emerging markets, and in predicting standard indicators of international business conditions. We show that an investor would have inexorably profited from using the forecasts provided by the GEA Tracker to weight a portfolio. Finally, the GEA Tracker allows us to present the daily evolution of global economic activity during the COVID-19 pandemic.
Keywords: F44; G17; Q02; 330; Global Economic Activity; Commodity Prices; Factor Models; Variable Selection; Genetic Algorithm; Leading Indicators